Long-Term Trends in the Saving-Investment Balance and Persistent Current Account Surpluses in a Small Open Economy : The Case of the Netherlands - Halikias, Ioannis (Washington, D.C. : International Monetary Fund, 1996)
This paper explores, from an investment-saving perspective, the factors underlying the persistent widening of the current account surplus in the Netherlands since the early 1980s. Standard intertemporal models, even appropriately extended to incorporate specific features of the Dutch economy, do not appear to fully account for this development. Accordingly, the paper focusses attention on the production side of the economy to gain further insight into the trends of the current account. Empirical evidence suggests that changes in relative factor prices and a relative demand shift toward non-tradable goods account for the bulk of the observed widening of the current account surplus. In turn, the impact of these factors on the current account appears to reflect both changes in factor proportions and deviations from perfect competition in the Dutch sheltered sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet